Positive electrode material for lithium secondary battery, method for producing the same, positive electrode for lithium secondary battery including the same, and lithium secondary battery

JP7632940B2Active Publication Date: 2025-02-19LG ENERGY SOLUTION LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022146975
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-09-19
Filing Date
2022-09-15
Publication Date
2025-02-19
Estimated Expiration
2038-09-19

AI Technical Summary

Benefits of technology

【0017】 本発明によれば、リチウムコバルト酸化物を含む第1正極活物質、及びリチウムニッケルコバルトマンガン酸化物を含む第2正極活物質を混合して使用することで、正極材の製造コストを低減することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632940000002
    Figure 0007632940000002
  • Figure 0007632940000003
    Figure 0007632940000003
  • Figure 0007632940000004
    Figure 0007632940000004
Patent Text Reader

Abstract

A first technical object of the present invention is to provide a cathode material for a lithium secondary battery that is low in cost and has improved life characteristics during high-speed charging. [Solution] The present invention relates to a cathode material including a first cathode active material represented by the following formula (1) and a second cathode active material represented by the following formula (2), wherein the second cathode active material has an electrical conductivity of 0.1 μS / cm to 150 μS / cm when compressed into a pellet at 400 kgf to 2,000 kgf, a method for producing the cathode material, a cathode for a lithium secondary battery including the cathode material, and a lithium secondary battery. LiCo 1-a M 1 a O2(1):M 1 is at least one selected from Al, Ti, Mg, and Zr, and 0≦a≦0.2. LiNi b Co c Mn d M 2 e O2(2):M 2 is at least one selected from Al, Ti, Mg, Zr, Y, Sr, and B, and 0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2017-0120679 filed on September 19, 2017, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a positive electrode material for a lithium secondary battery, a method for producing the positive electrode material, a positive electrode for a lithium secondary battery including the positive electrode material, and a lithium secondary battery including the same. [Background technology]

[0003] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among these secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, are commercially available and widely used.

[0004] Recently, research has been actively conducted to increase the capacity of such lithium secondary batteries and to shorten the charge / discharge time.

[0005] Conventionally, lithium transition metal composite oxides have been used as the positive electrode active material of lithium secondary batteries, and among them, lithium cobalt composite metal oxides such as LiCoO2 have a high operating voltage and can react with a high current due to effective desorption of lithium ions during high-speed charging, so that they can provide a positive electrode with excellent charging efficiency. However, LiCoO2 has poor thermal properties due to instability of the crystal structure caused by delithiation, and in particular, cobalt is expensive, so there is a limit to its mass use as a power source in fields such as electric vehicles.

[0006] Recently, lithium-cobalt composite metal oxide and low-cost lithium nickel-cobalt manganese oxide, Li(Ni a Co b Mn c)O2 (At this time, a, b, and c are atomic fractions of independent oxide composition elements or the like, where 0 < a < 1, 0 < b < 1, and 0 < c < 1), and attempts have been made to enhance the price competitiveness of the positive electrode material by mixing them.

[0007] However, in the case of a secondary battery to which a positive electrode material containing a lithium cobalt composite metal oxide and a lithium nickel cobalt manganese oxide is applied, in the section where the lithium nickel cobalt manganese oxide operates alone at the initial stage of charging during high-speed charging, there is a problem that an overload is applied to the lithium nickel cobalt manganese oxide and the life performance is deteriorated. Such problems occurred more frequently especially when nickel was contained in a high content.

[0008] Therefore, there is a demand for the development of a positive electrode material that can improve the life characteristics during high-speed charging by reducing the overload of the lithium nickel cobalt manganese oxide.

Summary of the Invention

Problems to be Solved by the Invention

[0009] In order to solve the above problems, the first technical problem of the present invention is to provide a positive electrode material for a lithium secondary battery that has low cost and improved life characteristics during high-speed charging.

[0010] The second technical problem of the present invention is to provide a method for manufacturing a positive electrode material that can shorten the single-operation section of the second positive electrode active material by increasing the charging resistance of the second positive electrode active material.

[0011] The third technical problem of the present invention is to provide a positive electrode for a lithium secondary battery including the positive electrode material.

[0012] The fourth technical problem of the present invention is to provide a lithium secondary battery including the positive electrode for a lithium secondary battery and having improved life characteristics during high-speed charging.

Means for Solving the Problems

[0013] The present invention provides a cathode material comprising: a first cathode active material represented by the following chemical formula (1); and a second cathode active material represented by the following chemical formula (2), wherein the second cathode active material has an electrical conductivity of 0.1 μS / cm to 150 μS / cm measured after compressing the second cathode active material under a rolling load of 400 kgf to 2,000 kgf to prepare it into a pellet: [Chemical formula (1)] LiCo 1-a M 1 a O2(1) [Chemical formula (2)] LiNi b Co c Mn d M 2 e O2(2) In the above chemical formula (1), M 1 is at least one selected from the group consisting of Al, Ti, Mg, and Zr, and 0≦a≦0.2; In the above chemical formula (2), M 2 is at least one selected from the group consisting of Al, Ti, Mg, Zr, Y, Sr, and B, and 0 <b≦0.6、0<c≦0.35、0<d≦0.35、0<e≦0.1である。

[0014] The present invention also relates to a method for producing a lithium-containing cobalt oxide, a lithium-containing raw material, and a doping element M 1 preparing a first positive electrode active material represented by the following chemical formula (1) by mixing and sintering the raw materials: nickel oxide, cobalt oxide, manganese oxide, doping element M 2 a step of mixing a lithium-containing raw material and a lithium-containing raw material in a solid phase and firing the mixture to produce a second positive electrode active material represented by the following chemical formula (2): and a step of mixing the first positive electrode active material and the second positive electrode active material, wherein the second positive electrode active material is compressed at a rolling load of 400 kgf to 2,000 kgf to produce a pellet, and the measured electrical conductivity of the second positive electrode active material is 0.1 μS / cm to 150 μS / cm: [Chemical formula (1)] LiCo1-a M 1 a O2(1) [Chemical formula (2)] LiNi b Co c Mn d M 2 e O2(2) In the above chemical formula (1), M 1 is at least one selected from the group consisting of Al, Ti, Mg, and Zr, and 0≦a≦0.2; In the above chemical formula (2), M 2 is at least one selected from the group consisting of Al, Ti, Mg, Zr, Y, Sr, and B, and 0 <b≦0.6、0<c≦0.35、0<d≦0.35、0<e≦0.1である。

[0015] The present invention also provides a positive electrode for a lithium secondary battery, which comprises the positive electrode material according to the present invention.

[0016] There is also provided a lithium secondary battery comprising the positive electrode according to the present invention. Effect of the Invention

[0017] According to the present invention, the manufacturing cost of the positive electrode material can be reduced by using a mixture of a first positive electrode active material containing lithium cobalt oxide and a second positive electrode active material containing lithium nickel cobalt manganese oxide.

[0018] In addition, when preparing the second positive electrode active material of the present invention, nickel oxide, cobalt oxide, and manganese oxide are composited using a solid-phase method, so that metal elements present in the second positive electrode active material may not be uniformly mixed at the atomic level, but may be mixed unevenly. As a result, during high-speed charging at 1C-rate or higher, the migration path of lithium ions may be obstructed, and the charging resistance of the second positive electrode active material may increase. Therefore, the start voltage of the second positive electrode active material increases, and the independent operating section of the second positive electrode active material is shortened, thereby reducing the overload of the second positive electrode active material, and a lithium secondary battery showing excellent life characteristics during high-speed charging can be provided using this. [Brief description of the drawings]

[0019] [Figure 1] 4 is a graph showing the change in electrical conductivity depending on the rolling load after the second positive electrode active materials prepared in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2 were compressed into pellets. [Diagram 2] 1 is a graph showing the charging profiles of the lithium secondary batteries produced in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2. [Diagram 3] 1 is a graph showing the cycle life characteristics of lithium secondary batteries produced in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention will now be described in further detail.

[0021] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a way that is consistent with the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.

[0022] In the past, a cathode material made of a mixture of lithium cobalt oxide and lithium nickel cobalt manganese oxide has been studied as a cathode material for lithium secondary batteries for high-speed charging. However, when a secondary battery using the cathode material is charged at a high speed of 1C-rate or higher, due to the different start-of-operation voltages of lithium cobalt oxide and lithium nickel cobalt manganese oxide, a section occurs in which the lithium nickel cobalt manganese oxide, which has a lower start-of-operation voltage, operates alone at the beginning of the high-speed charge. As such, high-speed charging at 1C-rate or higher applies an excessive current to the battery, which causes an overload in the section in which the lithium nickel cobalt manganese oxide operates alone, and the life characteristics of the secondary battery are reduced.

[0023] Therefore, the present inventors have found that it is possible to manufacture a lithium secondary battery having improved life characteristics during high-speed charging by mixing lithium cobalt oxide and lithium nickel cobalt manganese oxide at an appropriate mixing ratio and controlling the electrical conductivity of the lithium nickel cobalt manganese oxide to reduce manufacturing costs and increase the charging resistance of the lithium nickel cobalt manganese oxide and shorten the independent operating range of the lithium nickel cobalt manganese oxide, thereby completing the present invention.

[0024] To explain this in more detail, the cathode active material according to the present invention is a cathode material including a first cathode active material including lithium cobalt oxide and a second cathode active material including lithium nickel cobalt manganese oxide, and the second cathode active material has an electrical conductivity of 0.1 μS / cm to 150 μS / cm measured after compressing the second cathode active material under a rolling load of 400 kgf to 2,000 kgf to prepare it into a pellet shape.

[0025] Specifically, the first positive electrode active material may be represented by the following chemical formula (1): [Chemical formula (1)] LiCo 1-a M 1 a O2(1) In the above chemical formula (1), M 1 is at least one selected from the group consisting of Al, Ti, Mg, and Zr, and 0≦a≦0.2.

[0026] The first positive electrode active material is easy to manufacture and therefore can be mass-produced. It has an operation start voltage of 3.95V, has excellent capacity characteristics, and can exhibit stable life characteristics and output characteristics at high voltages.

[0027] The first positive electrode active material is a doping element M 1 In this case, the structural stability of the first positive electrode active material may be improved. For example, the first positive electrode active material may include a doping element M 1The doping element M may be present in an amount of 100 ppm to 10,000 ppm. 1 In the case where the first positive electrode active material contains LiCoO2 in the above content, the effect of improving the structural stability can be further improved. Preferably, the first positive electrode active material may contain at least one doping element selected from the group consisting of Al, Ti, and Mg, preferably two or more doping elements. For example, the first positive electrode active material may contain LiCoO2. e Ti 0.004 Mg 0.004 Al 0.004 May contain O2.

[0028] In addition, the first positive electrode active material may further include a coating layer including at least one coating element selected from the group consisting of Al, Ti, Mg, and Zr. For example, by further including the coating layer in the first positive electrode active material, the coating layer can prevent the first positive electrode active material from contacting with an electrolyte contained in a lithium secondary battery, thereby suppressing the occurrence of side reactions, thereby achieving an effect of improving life characteristics when applied to a battery.

[0029] The content of the coating element in the coating layer may be 100 ppm to 10,000 ppm, preferably 100 ppm to 5,000 ppm, more preferably 200 ppm to 2,000 ppm, based on the total weight of the first positive active material. For example, when the coating element is contained in the above range, the side reaction occurrence suppression effect is more effectively generated, and thus the life characteristics when applied to a battery can be further improved.

[0030] The coating layer may be formed on the entire surface of the first positive electrode active material or may be formed partially on the surface of the first positive electrode active material. Specifically, when the coating layer is formed partially on the surface of the first positive electrode active material, the coating layer may be formed on an area of ​​20% or more and less than 100% of the total surface area of ​​the first positive electrode active material.

[0031] The average particle size (D 50The average particle size (D) of the first positive electrode active material may be 10 μm or more, preferably 10 μm to 20 μm, and more preferably 10 μm to 18 μm. 50 When the diameter is 10 μm or more, a high energy density can be realized.

[0032] The average particle size (D 50 ) can be defined as the particle size at 50% of the particle size distribution. For example, the average particle size (D 50 ) can be measured using a laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes from the submicron range to several mm, and can provide results with high reproducibility and high resolution. For example, 50 The method for measuring the average particle size (D) at 50% of the particle size distribution measured by the measuring device is as follows: the first positive electrode active material is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and then the average particle size (D) at 50% of the particle size distribution measured by the measuring device is measured. 50 ) can be calculated.

[0033] Meanwhile, the second positive electrode active material is represented by the following chemical formula (2), and the second positive electrode active material is compressed under a rolling load of 400 kgf to 2,000 kgf to prepare a pellet, and then the measured electrical conductivity is 0.1 μS / cm to 150 μS / cm.

[0034] [Chemical formula (2)] LiNi b Co c Mn d M 2 e O2(2) In the above chemical formula (2), M 2 is at least one selected from the group consisting of Al, Ti, Mg, Zr, Y, Sr, and B, and 0 <b≦0.6、0<c≦0.35、0<d≦0.35、0<e≦0.1である。

[0035] Preferably, the second positive electrode active material is Li(Ni 0.50 Co 0.20 Mn 0.30 ) 0.998 Sr 0.002 O2, Li(Ni 0.50 Co 0.20 Mn 0.30 ) 0.998 Y 0.002 O2, Li(Ni 0.50 Co 0.30 Mn 0.20 ) 0.998 Y 0.002 O2, Li(Ni 0.50 Co 0.30 Mn 0.20 ) 0.998 Sr 0.002 O2, Li(Ni 0.60 Co 0.20 Mn 0.20 ) 0.998 Y 0.002 O2 and Li(Ni 0.60 Co 0.20 Mn 0.20 ) 0.998 Sr 0.002 O2.

[0036] The second positive electrode active material is a doping element M 2 doped lithium nickel cobalt manganese oxide, 2 The doping element M can promote grain growth or retard the desorption rate of lithium ions. 2 When doped with the doping element M 2 The grain growth of the second positive electrode active material may be promoted by the above-mentioned, so that the second positive electrode active material forms a monolithic structure.

[0037] The second positive electrode active material is a doping element M 2 In the above range, the doping element M may be contained in an amount of 500 ppm to 2,000 ppm. 2By including the second positive electrode active material, the grain growth promoting effect of the second positive electrode active material may be further improved, and the second positive electrode active material may be formed in a monolithic structure.

[0038] The second positive electrode active material is compressed under a rolling load of 400 kgf to 2,000 kgf to be manufactured into a pellet, and the measured electrical conductivity is 0.1 μS / cm to 150 μS / cm, more preferably 1 μS / cm to 100 μS / cm. If the measured electrical conductivity after the pellet satisfies the above range, the charging resistance of the second positive electrode active material is high. Specifically, the electrical conductivity is formed to be low at about 0.1 μS / cm to 150 μS / cm because metal elements (nickel, cobalt, and manganese) present in the second positive electrode active material are not uniformly mixed at the atomic level. As a result, the migration path of lithium ions in the second positive electrode active material is obstructed during high-speed charging, and the charging resistance of the second positive electrode active material is high. Due to such an increase in charging resistance, the second positive electrode active material cannot be operated at its original operation start voltage (3.70 V) and may be operated at a higher operation start voltage than before, such as 3.75 V or more, preferably 3.80 V to 3.95 V. When the second positive electrode active material is mixed with the first positive electrode active material and operated, the independent operation range of the second positive electrode active material is shortened, so that when the second positive electrode active material is applied to a secondary battery, overload of the second positive electrode active material can be prevented and the life characteristics during high-speed charging can be improved.

[0039] For example, if the electrical conductivity of the second positive active material measured after being manufactured into a pellet is less than 0.1 μS / cm, the second positive active material may not function as a positive electrode material because the mobility of lithium ions in the second positive active material is low due to the excessively low electrical conductivity. If the electrical conductivity of the second positive active material measured after being manufactured into a pellet exceeds 150 μS / cm, the charging resistance of the second positive active material is low, so that the independent operating range of the second positive active material cannot be shortened, and when this is applied to a secondary battery and fast charging is performed, the life span may be shortened.

[0040] Here, the charging resistance refers to a voltage value of a charging profile when charging at a high current of 1C-rate or more. In the present invention, when the voltage value of the charging profile increases by 0.2V or more compared to before charging, it is determined that the charging resistance has increased to a level that can prevent overload of the second positive electrode active material.

[0041] The electrical conductivity of the second positive electrode active material can be measured, for example, by compressing the second positive electrode active material at a rolling load of 400 kgf to 2,000 kgf, preferably 2,000 kgf, to produce a pellet, which is then introduced into a commercially available electrical conductivity measuring device (Powder Resistivity Measurement System, Loresta).

[0042] Furthermore, the second positive electrode active material may further include a coating layer containing at least one coating element selected from the group consisting of Al, Ti, Mg, Zr, Y, Sr, and B. For example, the coating layer may block contact between the second positive electrode active material and an electrolyte solution included in a lithium secondary battery, or may consume HF present in the electrolyte solution to suppress the occurrence of side reactions, thereby improving the life characteristics when applied to a battery and increasing the packing density of the positive electrode active material.

[0043] When the coating element is further included as described above, the content of the coating element in the coating layer may be 100 ppm to 10,000 ppm, preferably 100 ppm to 5,000 ppm, more preferably 200 ppm to 2,000 ppm, based on the total weight of the second positive electrode active material. For example, when the coating element is included in the above range based on the total weight of the second positive electrode active material, the side reaction occurrence suppression effect is more effectively generated, and thus the life characteristics when applied to a battery may be further improved.

[0044] The coating layer may be formed on the entire surface of the second positive electrode active material or may be formed partially on the surface of the second positive electrode active material. Specifically, when the coating layer is formed partially on the surface of the second positive electrode active material, the coating layer may be formed on an area of ​​20% or more and less than 100% of the total surface area of ​​the second positive electrode active material.

[0045] The average particle size (D 50 The average particle size (D) of the second positive electrode active material may be 8 μm or less, preferably 4 μm to 8 μm, and more preferably 5 μm to 7 μm. 50 When the thickness is 8 μm or less, the movement of Li ions is easy, but the resistance is increased to such an extent that the independent operating range of the second positive electrode active material is shortened, and the second positive electrode active material may be formed in the form of single particles rather than in the form of secondary particles in which primary particles are aggregated.

[0046] The average particle size (D 50 ) may be defined as a particle size at 50% of the particle size distribution, and the average particle size of the second positive electrode active material may be measured using the same method as the average particle size of the first positive electrode active material.

[0047] The crystal grain size of the second positive electrode active material may be 200 nm to 500 nm. When the crystal grain size of the second positive electrode active material satisfies this range, the charging resistance of the second positive electrode active material is increased and the independent operation section of the second positive electrode active material is shortened, and thus the secondary battery using the second positive electrode active material is less susceptible to overload, and thus the life and capacity characteristics can be improved when the secondary battery is charged at high speed. The crystal grain size of the second positive electrode active material may be measured using an XRD analyzer.

[0048] Meanwhile, in the present invention, the positive electrode material may contain a first positive electrode active material and a second positive electrode active material in a weight ratio of (40-90):(10-60), and preferably, the first positive electrode active material and the second positive electrode active material in a weight ratio of (50-80):(20-50). When the first positive electrode active material and the second positive electrode active material are contained in a weight ratio of (40-90):(10-60), an overload of the second positive electrode active material is prevented, thereby manufacturing a lithium secondary battery having excellent life characteristics during high-speed charging, and at the same time, manufacturing costs can be reduced.

[0049] Also, cobalt oxide, lithium-containing source material, and doping element M 1 preparing a first positive electrode active material represented by the following chemical formula (1) by mixing and sintering the raw materials: nickel oxide, cobalt oxide, manganese oxide, doping element M 2 a step of mixing a lithium-containing raw material and a lithium-containing raw material in a solid phase and firing the mixture to produce a second positive electrode active material represented by the following chemical formula (2): and a step of mixing the first positive electrode active material and the second positive electrode active material, wherein the second positive electrode active material is compressed at a rolling load of 400 kgf to 2,000 kgf to produce a pellet, and the measured electrical conductivity of the second positive electrode active material is 0.1 μS / cm to 150 μS / cm: [Chemical formula (1)] LiCo 1-a M 1 a O2(1) [Chemical formula (2)] LiNi b Co c Mn d M 2 e O2(2) In the above chemical formula (1), M 1 is at least one selected from the group consisting of Al, Ti, Mg, and Zr, and 0≦a≦0.2; and in the chemical formula (2), M 2is at least one selected from the group consisting of Al, Ti, Mg, Zr, Y, Sr, and B, and 0 <b≦0.6、0<c≦0.35、0<d≦0.35、0<e≦0.1である。

[0050] In order to prepare the cathode material according to the present invention, a first cathode active material represented by the above formula (1) is first prepared. The first cathode active material may be prepared by a conventional solid-phase method, and specifically, the first cathode active material is ... 1 The raw materials are mixed and fired to produce the first positive electrode active material represented by the above chemical formula (1).

[0051] For example, the cobalt oxide may include at least one selected from the group consisting of Co3O4, CoOOH, and Co(OH)2.

[0052] For example, the lithium-containing raw material is not particularly limited as long as it is a compound containing a lithium source, but preferably, at least one selected from the group consisting of lithium carbonate (Li2CO3), lithium hydroxide (LiOH), LiNO3, CH3COOLi, and Li2(COO)2 may be used.

[0053] The cobalt oxide and the lithium-containing raw material may be mixed in a molar ratio of 1:1.00 to 1:1.10, preferably in a molar ratio of 1:1.02 to 1:1.08. When the cobalt oxide and the lithium-containing raw material are mixed in the above range, the produced positive electrode active material may exhibit excellent capacity.

[0054] The lithium-containing raw material may be determined depending on the content of lithium and metal (Co) in the finally prepared positive electrode active material, and may be used in an amount such that the molar ratio of lithium contained in the lithium-containing raw material to cobalt contained in the cobalt oxide (Li / Co molar ratio) is 1.00 or more, preferably 1.02 to 1.08. When the molar ratio of the lithium-containing raw material and the cobalt oxide satisfies the above range, the prepared positive electrode active material may exhibit excellent capacity.

[0055] The doping element M 1 The raw material may contain 100 ppm to 10,000 ppm, preferably 100 ppm to 5,000 ppm of the doping element M in the above range. 1 By including the doping element M, the surface resistance can be increased and the rate of desorption of lithium ions can be delayed, thereby improving the structural stability and life of the battery manufactured using the doping element M. 1 The raw material may include at least one metal element selected from the group consisting of Al, Ti, Mg, and Zr. 1 The raw material may include at least one selected from the group consisting of Al2O3, TiO2, MgO, and ZrO2.

[0056] The calcination may be carried out at a temperature of 900° C. to 1,100° C., preferably 950° C. to 1,080° C. When the calcination temperature is within the above range, the raw material does not remain in the particles, so that the high temperature stability of the battery can be improved, and the volume density and crystallinity are improved, so that the structural stability of the first positive electrode active material can be improved. In addition, the particles of the positive electrode active material grow uniformly, so that the volume capacity of the battery can be improved.

[0057] The calcination may be performed for 2 hours to 24 hours, preferably 5 hours to 12 hours. When the calcination time is within the above range, a first positive electrode active material with high crystallinity can be obtained, and production efficiency can also be improved.

[0058] On the other hand, nickel oxide, cobalt oxide, manganese oxide, and doping element M 2 and a lithium-containing raw material are mixed in a solid phase and sintered to produce the second positive electrode active material represented by the chemical formula (2).

[0059] For example, the nickel oxide may include at least one selected from the group consisting of NiO, Ni(OH)2, and NiOOH.

[0060] For example, the cobalt oxide may include at least one selected from the group consisting of Co3O4, CoOOH, and Co(OH)2.

[0061] For example, the manganese oxide may include at least one selected from the group consisting of Mn2O3, MnO2, Mn3O4, and MnO.

[0062] The lithium-containing source material is not particularly limited as long as it is a compound containing a lithium source, but preferably, at least one selected from the group consisting of lithium carbonate (Li2CO3), lithium hydroxide (LiOH), LiNO3, CH3COOLi, and Li2(COO)2 may be used.

[0063] In the step of preparing the second positive electrode active material, nickel, cobalt, manganese, lithium, and a doping element M 2 The molar ratio of nickel, cobalt, manganese, lithium, and doping element M may be (40-60):(20-30):(20-30):(100-104):(0-2), preferably (50-60):(20-30):(20-30):(102-103):(0-1). 2When mixed in a solid state to have a molar ratio within the above range, a positive electrode active material containing more than 60% nickel can have a stable life performance even when driven at a high voltage of 4.3V or more.

[0064] When lithium nickel cobalt manganese oxide is synthesized using a solid phase method as in the present invention, the charging resistance of the second positive electrode active material may be high. More specifically, nickel oxide, cobalt oxide, manganese oxide, doping element M 2 When the lithium-containing raw material and the lithium-containing raw material are mixed and sintered, the nickel, cobalt, and manganese elements present in the second positive electrode active material are not uniformly mixed at the atomic level, and thus, during high-speed charging at 1C-rate or higher, the migration path of lithium ions is obstructed by the metal elements aggregated in the second positive electrode active material, which may increase the charging resistance of the second positive electrode active material.

[0065] The second positive electrode active material contains the doping element M 2 The raw material may be doped with 2,000 ppm to 10,000 ppm, preferably 3,000 ppm to 9,000 ppm. 2 By doping the raw material, the grain growth of the second positive electrode active material can be promoted, the second positive electrode active material can be formed into a single body structure, or the desorption rate of lithium ions from the second positive electrode active material can be delayed. For example, the doping element M 2 The raw material may include at least one metal element selected from the group consisting of Al, Ti, Mg, Zr, Y, Sr, and B. Specifically, the doping element M 2 The source material may include at least one selected from the group consisting of Al2O3, TiO2, MgO, ZrO2, Y2O3, SrO, and H3BO3.

[0066] The calcination may be performed at a temperature of 850° C. to 1,050° C., preferably 900° C. to 1,000° C. When the calcination temperature satisfies this range, the raw material does not remain in the particles, so that the high temperature stability of the battery can be improved, and thus the volume density and crystallinity can be improved, and as a result, the structural stability of the second positive electrode active material can be improved.

[0067] The calcination may be performed for 2 hours to 24 hours, preferably 5 hours to 12 hours. When the calcination time is within this range, a highly crystalline second positive electrode active material can be obtained, and production efficiency can also be improved.

[0068] Finally, the first positive electrode active material and the second positive electrode active material are mixed. At this time, the first positive electrode active material and the second positive electrode active material are mixed in a weight ratio of (40-90):(10-60), preferably (50-80):(20-50). The mixing is not particularly limited as long as the first positive electrode active material and the second positive electrode active material can be mixed uniformly. By mixing the first positive electrode active material and the second positive electrode active material in the above range, a lithium secondary battery having excellent life characteristics during high-speed charging can be manufactured, and the manufacturing cost can be reduced.

[0069] In addition, a positive electrode for a lithium secondary battery is provided, comprising the positive electrode material according to the present invention. Specifically, the positive electrode for the secondary battery comprises a positive electrode current collector and a positive electrode material layer formed on the positive electrode current collector, the positive electrode material layer comprising the positive electrode material according to the present invention.

[0070] In this case, by using a cathode material including the same first and second cathode active materials as described above as the cathode material, the start voltage of operation of the second cathode active material is increased, and a cathode in which overload of the second cathode active material is prevented is provided.

[0071] At this time, since the cathode material is the same as that described above, detailed description will be omitted, and only the remaining components will be described in detail below.

[0072] The positive electrode current collector is not particularly limited as long as it is conductive without inducing a chemical change in the battery, and may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode material. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0073] The positive electrode layer may contain, in addition to the positive electrode material, a conductive material and, optionally, a binder as required.

[0074] At this time, the positive electrode material may be included in a content of 80 to 99 wt %, more specifically, 85 to 98.5 wt %, based on the total weight of the positive electrode layer. When included in this content range, excellent capacity characteristics can be exhibited.

[0075] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electrical conductivity without causing chemical changes in the battery. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like. One or a mixture of two or more of these may be used. The conductive material may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode material layer.

[0076] The binder serves to improve adhesion between particles of the positive electrode material and between the positive electrode material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 0.1 to 15 wt % based on the total weight of the positive electrode material layer.

[0077] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode material. Specifically, the positive electrode may be manufactured by applying a composition for forming a positive electrode material layer, which is prepared by dissolving or dispersing the positive electrode material, and optionally a binder and a conductive material, in a solvent, onto a positive electrode current collector, followed by drying and rolling.

[0078] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the cathode material, conductive material, and binder in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can provide excellent thickness uniformity when applied to manufacture the cathode.

[0079] As another method, the positive electrode may be produced by casting the positive electrode material layer forming composition on a separate support, peeling the composition from the support, and then laminating the resulting film on a positive electrode current collector.

[0080] The present invention also provides an electrochemical device including the positive electrode, which may be a battery, a capacitor, or the like, and more specifically a lithium secondary battery.

[0081] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is the same as that described above, detailed description thereof will be omitted and only the remaining components will be described in detail below.

[0082] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly including the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0083] The lithium secondary battery according to the present invention includes a cathode containing the cathode material according to the present invention, and thus the start voltage of operation of the second cathode active material is increased and overload of the second cathode active material is prevented, thereby providing a lithium secondary battery having improved life characteristics during fast charging. Here, the fast charging refers to a method of charging a battery having a driving voltage of 3 V to 4.35 V at a high current of 1 C-rate or more, preferably 1 C-rate to 1.5 C-rate.

[0084] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0085] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0086] The negative electrode active material layer includes a negative electrode active material and, optionally, a binder and a conductive material.

[0087] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. Also, a thin film of metallic lithium may be used as the negative electrode active material. Also, both low crystalline carbon and high crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0088] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0089] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0090] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fibers or metal fibers; metal powders such as carbon fluoride, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives.

[0091] For example, the negative electrode active material layer may be produced by applying a composition for forming a negative electrode active material layer, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the composition. Alternatively, the negative electrode active material layer may be produced by casting the composition for forming a negative electrode active material layer onto a separate support, peeling the composition from the support, and laminating the resulting film onto the negative electrode current collector.

[0092] The negative electrode active material layer may be manufactured, for example, by applying a composition for forming a negative electrode active material layer, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the composition; or by casting the composition for forming a negative electrode active material layer onto another support, peeling the composition from the support, and laminating the resulting film onto the negative electrode current collector.

[0093] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, may be used. In addition, a separator coated with a ceramic component or a polymer material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0094] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0095] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0096] The organic solvent may be any organic solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move, without any particular limitation. Specific examples of the organic solvent include ester-based solvents such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, γ-butyrolactone, and ε-caprolactone; ether-based solvents such as dimethoxyethane, diethoxyethane, dibutyl ether, and tetrahydrofuran; ketone-based solvents such as cyclohexanone; aromatic hydrocarbon-based solvents such as benzene and fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), and ethylene carbonate (ethylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (EC) and propylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a hydrocarbon group having a linear, branched or cyclic structure with 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of the battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.In this case, the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, which can provide excellent electrolyte performance.

[0097] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within a range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0098] In addition to the electrolyte components, the electrolyte may further include one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be included in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.

[0099] As described above, the lithium secondary battery including the cathode material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0100] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0101] The battery module or the battery pack may be used as a power source for one or more medium- to large-sized devices including a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0102] The shape of the lithium secondary battery of the present invention is not particularly limited, but may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0103] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a large number of battery cells.

[0104] Hereinafter, the present invention will be described in detail with reference to the embodiments. However, the embodiments according to the present invention may be modified in several different forms, and the scope of the present invention should not be interpreted as being limited to the embodiments described below. The embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. EXAMPLES

[0105] Example 1 [Production of cathode materials] 100 g of Co3O4, 47 g of Li2CO3, 0.4069 g of TiO2, 0.2858 g of MgO2, and 0.2304 g of Al2O3 were mixed in the solid phase using a ball mill and sintered at 1,050 °C for 9 hours to obtain Ti, Mg, and Al doped lithium cobalt oxide (LiCo 0.988 Ti 0.004 Mg 0.004 Al 0.004 The Ti, Mg, and Al doped lithium cobalt oxide prepared above was used as the first positive electrode active material.

[0106] 46.41 g of NiO, 19.95 g of CoO, 29.43 g of MnO, 47.29 g of LiCO, and 0.193 g of SrO were mixed and sintered at 990° C. for 10 hours to obtain a Sr-doped lithium nickel cobalt manganese oxide (nickel:cobalt:manganese molar ratio=5:2:3, NCM523) with an average particle size of 5.8 μm, which was used as the second positive electrode active material.

[0107] A positive electrode composition was prepared by mixing 96 parts by weight of a positive electrode material obtained by mixing the first positive electrode active material and the second positive electrode active material in a weight ratio of 7:3, 2 parts by weight of a denka black conductive material, and 2 parts by weight of a polyvinylidene fluoride (PVDF) binder in an NMP solvent.

[0108] The composition for forming a positive electrode prepared above was applied to an aluminum foil having a thickness of 20 μm, dried, and roll-pressed to prepare a positive electrode.

[0109] Meanwhile, 95.6 parts by weight of artificial graphite as a negative electrode active material, 0.75 parts by weight of carbon black as a conductive material, and 3.65 parts by weight of carboxymethyl cellulose (CMC) as a binder were mixed and added to a solvent, H2O, to prepare a composition for forming a negative electrode. The composition for forming a negative electrode was applied onto a copper foil having a thickness of 20 μm, dried, and then roll-pressed to prepare a negative electrode.

[0110] The positive and negative electrodes prepared above were laminated together with a polyethylene separator to prepare an electrode assembly, which was then placed in a battery case. An electrolyte solution prepared by dissolving 1.0 M LiPF6 in a mixed solvent of ethylene carbonate:propyl propionate:diethyl carbonate in a ratio of 3:1:6 was then injected to prepare a lithium secondary battery.

[0111] Example 2 A first positive electrode active material, a positive electrode, a negative electrode, and a lithium secondary battery including the same were prepared in the same manner as in Example 1, except that in the preparation of the second positive electrode active material, ZrO was doped instead of SrO to prepare a second positive electrode active material having an electrical conductivity of 82.2 μS / cm.

[0112] Comparative Example 1 When preparing the second positive electrode active material, NiSO4, CoSO4, and MnSO4 were mixed in an amount such that the molar ratio of nickel:cobalt:manganese was 5:2:3 in H2O solvent to prepare a transition metal-containing solution with a concentration of 2M.

[0113] The vessel containing the transition metal-containing solution was connected to a 5 L batch reactor. In addition, a 4 molar NaOH aqueous solution and a 7 wt% NH4OH aqueous solution were prepared and connected to the batch reactor, respectively. After 3 L of deionized water was added to the batch reactor, nitrogen gas was purged into the reactor at a rate of 2 L / min to remove dissolved oxygen in the water and create a non-oxidizing atmosphere inside the reactor.

[0114] The transition metal-containing solution, the NaOH aqueous solution, and the NH4OH aqueous solution were respectively fed into a batch reactor at rates of 180 mL / min, 180 mL / min, and 10 mL / min, and co-precipitated for 12 hours to precipitate nickel manganese cobalt hydroxide particles at a pH of 12. The precipitated nickel manganese cobalt hydroxide particles were separated and washed, and then dried in an oven at 120° C. for 12 hours to prepare a precursor for a second positive electrode active material.

[0115] The obtained precursor was dry mixed with LiOH·H2O (1.04 mol of LiOH per 1 mol of precursor) and calcined at 990°C for 9 hours to prepare lithium nickel cobalt manganese oxide (nickel:cobalt:manganese molar ratio = 5:2:3, NCM523). Except for using this as a second positive electrode active material, a first positive electrode active material, a positive electrode, a negative electrode, and a lithium secondary battery including the same were prepared in the same manner as in Example 1.

[0116] Comparative Example 2 A first positive electrode active material, a positive electrode, a negative electrode, and a lithium secondary battery including the same were prepared in the same manner as in Comparative Example 1, except that in preparing the second positive electrode active material, a nickel-cobalt-manganese hydroxide precursor was used, which was prepared by changing the co-precipitation reaction time from 12 hours to 0.5 hours.

[0117] Experimental example 1: Measurement of electrical conductivity The second positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were compressed into pellets at rolling loads of 400 kgf, 800 kgf, 1200 kgf, 1600 kgf, and 2,000 kgf, respectively, and the electrical conductivity of the second positive electrode active materials was measured using a Powder Resistivity Measurement System (Loresta) as shown in Table 1 and FIG. 1 below.

[0118] [Table 1]

[0119] In this regard, FIG. 1 is a graph showing the change in electrical conductivity of the pellet-shaped second positive electrode active material depending on the rolling load after compressing the second positive electrode active material prepared in Examples 1-2 and Comparative Examples 1-2 into a pellet shape. As shown in FIG. 1, it was confirmed that the second positive electrode active material according to Examples 1 and 2 showed a low electrical conductivity of 100 μS / cm or less regardless of the rolling load. In the case of Example 2, by applying Zr doping instead of Sr which promotes grain size growth, the effect of grain size growth during sintering was small, so the size of the crystal grains was reduced, and the electrical conductivity was increased compared to Example 1. On the other hand, it was confirmed that the electrical conductivity of the second positive electrode active material according to Comparative Examples 1 and 2 increased as the rolling load for compressing the second positive electrode active material increased. This was confirmed to be because the second positive electrode active material was synthesized by a wet method using a co-precipitation precursor in Comparative Examples 1 and 2, and thus the second positive electrode active material had excellent mixing uniformity and high electrical conductivity. In particular, when the coprecipitation reaction was performed for a short time as in Comparative Example 2, the particle size of the precursor was reduced, and therefore the particle size of the final positive electrode active material after calcination was also reduced. As a result, the electrical conductivity of the positive electrode active material in Comparative Example 2 was higher than that of Comparative Example 1. That is, when the second positive electrode active material was synthesized using a dry method as in Examples 1 and 2, the mixing uniformity was reduced compared to Comparative Examples 1 and 2, and the particles of the second positive electrode active material were locally aggregated, and therefore the electrical conductivity of the second positive electrode active material prepared in pellet form was also confirmed to be low at 100 μS / cm or less.

[0120] Experimental example 2: Measuring the charging profile The charging profiles of the lithium secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2 at room temperature of 25° C. and 4.35 V were measured.

[0121] Specifically, the lithium secondary batteries prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were charged at a constant current of 1.0 C to 4.35 V at room temperature of 25° C. with a cut-off of 0.05 C, and the charging profiles of the lithium secondary batteries according to Examples 1 and 2 and Comparative Examples 1 and 2 were measured.

[0122] In this regard, FIG. 2 is a graph showing the charging profile of the lithium secondary battery prepared in Examples 1-2 and Comparative Examples 1-2 of the present invention. Among them, the part indicated by the dotted circle is the independent operation section of the second positive electrode active material at the beginning of the high-speed charge. As shown in FIG. 2, it was confirmed that the independent operation section of the second positive electrode active material was shortened in Examples 1 and 2 compared to Comparative Examples 1 and 2. This is because, when the second positive electrode active material is prepared by the solid-phase mixing method as in Examples 1 and 2, the metal elements present in the second positive electrode active material were not uniformly mixed. As a result, in the case of the second positive electrode active material prepared in Examples 1-2, the movement of lithium ions is hindered in the second positive electrode active material, so that charging is not easy compared to Comparative Examples 1 and 2 in which the metal elements are uniformly mixed, and therefore the operation start voltage of the second positive electrode active material in Examples 1 and 2 is increased.

[0123] That is, as in Examples 1 and 2, it was confirmed that as the operation start voltage of the second positive electrode active material increased, the section in which the second positive electrode active material alone operated was shortened.

[0124] Therefore, it is expected that the use of the lithium secondary batteries of Examples 1 and 2 can solve the overload problem caused by the shortening of the independent operation range of the second positive active material.

[0125] Experimental example 3: Evaluation of life characteristics The life characteristics of the lithium secondary batteries produced in Examples 1 and 2 and Comparative Examples 1 and 2 were measured at room temperature of 25° C. and 4.35 V.

[0126] Specifically, the lithium secondary batteries prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were charged at a constant current of 1.0 C to 4.35 V with a cut-off of 0.05 C at room temperature of 25° C., and then discharged at a constant current of 0.5 C to 3.0 V. The above charge and discharge behavior was counted as one cycle, and this cycle was repeated 80 times, after which the life characteristics of the lithium secondary batteries according to Examples 1 and 2 and Comparative Examples 1 and 2 were measured.

[0127] In this regard, FIG. 3 is a graph showing room temperature life characteristics according to cycles at 4.35V of the lithium secondary batteries manufactured in Examples 1 and 2 and Comparative Examples 1 and 2 of the present invention. As shown in FIG. 3, it was confirmed that the lithium secondary batteries according to Examples 1 and 2 exhibited about 95% of the initial capacity during 80 repeated charge and discharge cycles. However, it was confirmed that the lithium secondary batteries according to Comparative Examples 1 and 2 exhibited a capacity lower than 95%. That is, it was confirmed that the life characteristics of the lithium secondary battery deteriorated as the electrical conductivity value of the second positive electrode active material manufactured in pellet form as in Comparative Examples 1 and 2 increased. This is because the lower the charging resistance of the second positive electrode active material, the longer the independent operation section of the second positive electrode active material at the beginning of high-speed charging of the lithium secondary battery becomes, thereby increasing the problem of overload of the second positive electrode active material. It was confirmed that the side reaction of the electrolyte increases and the life characteristics deteriorate.

Claims

1. A first positive electrode active material represented by the following chemical formula (1): A positive electrode material comprising a second positive electrode active material represented by the following chemical formula (2): The first positive electrode active material and the second positive electrode active material are contained in a weight ratio of (40 to 90):(10 to 60), The second positive electrode active material has an operation start voltage of 3.75 V or more; The start-of-operation voltage is measured under charging conditions of 1C-rate or higher. [Chemical formula 1] LiCo 1-a M 1 a O 2 (1) [Chemical formula 2] L)) b Co c Mn d M 2 e O 2 (2) In the above chemical formula (1), M 1 is at least one selected from the group consisting of Al, Ti, Mg, and Zr, and 0≦a≦0.2; In the above chemical formula (2), M 2 is at least one selected from the group consisting of Al, Ti, Mg, Zr, Y, Sr, and B, and 0<b≦0.6, 0<c≦0.35, 0<d≦0.35, and 0<e≦0.

1.

2. The average particle size (D 50 2. The cathode material according to claim 1, wherein the thickness of the first layer is 10 μm or more.

3. The average particle size (D 50 3. The cathode material according to claim 1, wherein the thickness of the first layer is 8 μm or less.

4. The second positive electrode active material contains a doping element M 2 The positive electrode material according to any one of claims 1 to 3, comprising 2,000 ppm to 10,000 ppm of

5. The cathode material according to claim 1 , wherein the second cathode active material has a crystal grain size of 200 nm to 500 nm.

6. Cobalt oxide, lithium-containing source material, and doping element M 1 mixing and firing the raw materials to prepare a first positive electrode active material represented by the following formula (1); Nickel oxide, cobalt oxide, manganese oxide, doping element M 2 mixing the lithium-containing raw material and the lithium-containing raw material in a solid phase and firing the mixture to prepare a second positive electrode active material represented by the following formula (2): mixing the first positive electrode active material and the second positive electrode active material; The first positive electrode active material and the second positive electrode active material are mixed in a weight ratio of (40 to 90):(10 to 60), The second positive electrode active material has an operation start voltage of 3.75 V or more; The operation start voltage was measured under charging conditions of 1C-rate or more. [Chemical formula (1)] LiCo 1-a M 1 a O 2 (1) [Chemical formula (2)] L)) b Co c Mn d M 2 e O 2 (2) In the above chemical formula (1), M 1 is at least one selected from the group consisting of Al, Ti, Mg, and Zr, and 0≦a≦0.2; In the above chemical formula (2), M 2 is at least one selected from the group consisting of Al, Ti, Mg, Zr, Y, Sr, and B, and 0<b≦0.6, 0<c≦0.35, 0<d≦0.35, and 0<e≦0.

1.

7. In the step of preparing the second positive electrode active material, nickel, cobalt, manganese, lithium, and a doping element M 2 The method for producing a positive electrode material according to claim 6, wherein the molar ratio of the above is (40-60):(20-30):(20-30):(100-104):(exceeding 0 and not more than 2).

8. A positive electrode for a lithium secondary battery, comprising the positive electrode material according to any one of claims 1 to 5.

9. A lithium secondary battery comprising the positive electrode according to claim 8.

Citation Information

Patent Citations

  • High-voltage ternary lithium ion cathode material of single crystal morphology and preparation method thereof

    CN106229489A

  • Positive electrode active material for nonaqueous lithium secondary battery, manufacturing method thereof, and nonaqueous lithium secondary battery using the positive electrode active material

    JP2005346956A

  • Cathode active material, its manufacturing method and cathode as well as lithium cell using the material

    JP2006228733A

  • battery

    JP2007128723A

  • Manufacturing method of positive electrode active material for lithium secondary battery, positive electrode active material for lithium secondary battery, and nonaqueous lithium secondary battery using it

    JP2007280723A